Helipot Microcircuit Diode Driver and Sperry Buffer Amplifier with coin - Dietrich, T. A. (1950)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products.
Keywords: Coins; Microelectronics; Beckman Instruments, Inc.